Molecular Recognition of Polyaromatic Hydrocarbons (PAHs) by Naphthalene Dioxygenase through the Action of Rhamnolipid: PAHs Recognition by NDO with Rhamnolipid - Azhary, Nabihah; Abdul Hamid, Azzmer Azzar; Mohd Ashaari, Mardiana (Journal of Tropical Life Science, 2024)
Rhamnolipids are a type of glycolipid biosurfactant that has garnered significant attention in various industries, including healthcare and petroleum. Their remarkable properties, such as highly biodegradable and good emulsification, have propelled extensive research on their potential role in the biodegradation of polycyclic aromatic hydrocarbons (PAHs). While numerous empirical studies have focused on PAH biodegradation, the molecular interactions between biosurfactants and PAHs remain elusive. This study aims to provide insights into the molecular recognition of PAHs by naphthalene dioxygenase (NDO) in the presence of rhamnolipid by molecular docking and molecular dynamics (MD) simulations. The results indicated that selected PAH compounds, phenanthrene (PHE), fluoranthene (FLU), and benzo[a]pyrene (BAP), interact with NDO’s active site mostly through hydrophobic interactions. The presence of rhamnolipid changes NDO’s structural conformation, which leads to a more stable binding between PAHs and NDO, as demonstrated during simulation runs. In addition, the MD simulation analysis by using root-mean-square deviation (RMSD), root-mean-square fluctuation (RMSF), solvent accessible surface area (SASA), and minimum distance parameters for the systems with rhamnolipid provided better results compared to the system without rhamnolipid, especially for NDO-BAP complex. Moreover, the number of consensuses interacting residues (Phe224, His195, Leu307) for the NDO-BAP complex with rhamnolipid presence was higher compared to without rhamnolipid (Val209, Leu253). Phe224 was identified as a consensus interacting residue for the NDO-BAP complex with rhamnolipid; assuming its important role for substrate binding when rhamnolipid is present. Hence, this study offers molecular insights into the role of biosurfactants during hydrocarbon degradation, especially for high molecular weight PAHs.